Palladium-Catalyzed Annulation of 2,2′-Dibromobiphenyls with Alkynes: Synthesis of Functionalized Phenanthrenes and Dibenzochrysenes - Ma, Jun; Li, Gaoqiang; Qiao, Yan; Tu, Jingxuan; Liu, Sha; Xu, Feng (Synlett, 2015)
A palladium-catalyzed annulation process of 2,2′-dibromobiphenyls with alkynes for the synthesis of functionalized phenanthrenes has been realized. The methodology provides an efficient approach to dibenzochrysene derivatives starting from simple reactants in two steps.
Keywords: alkynes; annulations; domino reaction; fused-ring systems; palladium